Prevalence of trachoma and risk factors for disease in Benue State, Nigeria - Tagoh, Selassie (Department of Public Health and Family Medicine, 2019)
Background: Trachoma is a common contagious bacterial eye infection caused by Chlamydia trachomatis serovariants A, B, Ba or C. It is the leading infectious cause of blindness worldwide and is responsible for about 3% of global blindness. World Health Organization (WHO) reports suggest that of the 2.2 million people who have been rendered visually impaired worldwide by trachoma, 1.2 million are irreversibly blind while an additional 7.3 million people are suffering from trachomatous trichiasis (TT) and are at risk of developing blindness. According to WHO 2007 reports, globally about 84 million people suffer from active trachoma while an estimated 299 million people still live in trachoma endemic districts. In order to eliminate trachoma as a public health problem, The Global Trachoma Mapping Project (GTMP) was initiated on 23 July 2012 as a first step in generating population-level prevalence estimates of the disease so as to determine the need for intervention. Between 2013 and 2015, the GTMP mapped suspected endemic districts including Benue state of Nigeria. This current study took advantage of this data to generate prevalence information on Trachomatous inflammation Follicular (TF) and Trichiasis for Benue state and to describe the some of the household risk factors associated with the disease. The thesis is structured in three parts 0(Preamble), A (Protocol), B (Literature Review), C (Article) and D (Appendix). Methods: A two-stage cluster random sampling technique was utilized in a population based prevalence survey to generate estimates for TF and Trichiasis. Results: Overall unadjusted prevalence of TF among persons 1-9 years was 2.00% (95% CI: 1.20 – 2.98) and that of trichiasis among persons ≥15 years was 0.11% (95% CI 0.06 – 0.12). Trichiasis was more prevalent among adult women 0.05% (95% CI: 0.03 – 0.07) compared to males 0.03 % (95% CI: 0.02 – 0.05), (p=0.13). LGA-level prevalence of TF and Trichiasis among persons 1-9 years and persons ≥15 years ranged from 0.30% (95% CI: 0.1–0.5) to 5.30% (95% CI: 3.30–7.70) and 0.00% to 0.35% (95% CI: 0.12–0.50) respectively. Two LGAs had trichiasis prevalence above 0.2%. TF prevalence was between 5% and 9.9% in 2 LGAs. The common risk factors identified included age, sex, inaccessibility to water and latrine facility. Adults ≥15 years were 8.94(95%CI: 2.79 – 29.64) times more likely to have trichiasis compared to persons between 1-9 years of age. Conclusion: Trachoma was found to be a public health problem in 3 LGAs of Benue state. One round of mass antibiotic distribution will be required in 2 LGAs. With an estimated trichiasis backlog of 1,064, about 173 individuals with trichiasis needed to be managed to reduce the prevalence to less than the elimination threshold.